Using species distribution modelling in identifying locations for habitat restoration, relocations and potential ecological traps for the sand lizard, Lacerta agilis, in Northern Germany - David Bennett; Tim Diekötter (European Journal of Wildlife Research, 2025)
The sand lizard Lacerta agilis is a species of conservation concern in many areas, primarily due to habitat loss and fragmentation. Wildflower compensation areas, an increasingly widespread method of supporting biodiversity in intensive agricultural landscapes, could theoretically support L. agilis but may also act as an ecological trap. Using species distribution modelling, we estimated the relative habitat suitability for L. agilis across Schleswig Holstein. We then performed field studies at 41 wildflower sites (with varying levels of relative suitability) over two years using reptile mats, and a follow up survey with conservation detection dogs at four more sites. Ultimately, no L. agilis were observed at any site, regardless of method. However, the response curves and variable response curves indicate that permanent semi natural habitat has a strong positive influence on relative suitability. This could indicate that longer term measures are a better option for the conservation of this species.